Outcomes following patent foramen ovale percutaneous closure according to the delay from last ischemic event. (3rd October 2022) - Guedeney, P; Mesnier, J; Michel, M; Hauguel-Moreau, M; Silvain, J; Houde, C; Alperi, A; Panagides, V; Collet, J P; Wallet, T; Rouanet, S; Hammoudi, N; et al.
Abstract: Background: Randomized controlled trials evaluating patent foramen ovale (PFO) percutaneous closure only included patients with recent embolic event. We aimed to evaluate outcomes following percutaneous PFO closure outcomes according to the delay from the last embolic episode. Methods: This international ambispective cohort included consecutive patients from two centers in France and Canada undergoing PFO percutaneous closure for secondary prevention of paradoxical embolic event. The primary endpoint was the composite of stroke or transient ischemic attack (TIA). Logistic regression model was used to evaluate determinants of late PFO closure procedures. Results: A total of 1, 179 patients (mean age 49±12.7 years; 44.4% female) underwent PFO closure from 2001 to 2021 (Figure 1). The median delay from last embolic event to procedure was 6.0 (3.4–11.2) months. Determinants of late PFO closure procedure were the center (France versus Canada) adjusted Odds Ratio (aOR) 1.65 95% confidence interval (CI) 1.25–2.19, year of procedure (≥2018 versus <2018) aOR 1.43 95% CI 1.08–1.90, female sex aOR 1.63 95% CI 1.28–2.07 and lower RoPE score aOR 1.10 95% CI 1.03–1.19. After a median follow-up of 2.61 (1.13–7.25) years, the incidence rate of first stroke or TIA did not differ between early and late PFO procedures with 0.51 versus 0.29 events per 100 patient-years, respectively, incidence rate ratio 1.74 95% CI 0.66–5.08, p=0.25 (Figure 2). In univariate analysis, late PFO percutaneous closure was not associated with the occurrence of stroke or TIA, with hazard ratio 0.54 95% CI 0.22–1.34 p=0.17. Conclusion: This analysis provides indirect evidence that delay from last ischemic event does not impact outcomes following PFO percutaneous closure for secondary prevention. Funding Acknowledgement: Type of funding sources: None.